Pengembangan Kreativitas Guru dalam Proses Pembelajaran - Humaidi Humaidi; Moh. Sain (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2020)
Creativity is a key oriented towards the effectiveness of the learning process carried out by the teacher in achieving learning and educational goals. This study aims to reveal the teachers' creativity in the learning process. Teacher's creativity is the skills to have such as skills in making teaching materials, carrying out learning in class properly, learning methods that are relevant to the material, appropriate learning media, quality learning resources related to the discussion, etc. The research method used was a qualitative descriptive approach, and the research subjects are teachers in schools who expected to have creativity in the form of quality skills.